Modulatory effects of lysine and methionine in diets on growth and transcripts associated with immunity genes in broiler - Lee, Chai Yan (2019)
The poultry industry is one of the most advanced livestock industries in the world. Feed formulation is highly emphasized because the cost of feed is the biggest proportion (65-70%) of the production cost. One of the most economical ways to reduce feed cost is by efficiently meeting the nutritional requirement of the broilers. Alternative feed formulation includes supplementing amino acids with reduced levels of dietary crude protein which is more economical as it can reduce the cost of feed. In this study, the effects of amino acids supplementation of lysine and methionine in a low crude protein diet on the growth performance and expression of immunity genes including mucin 2 (MUC2), SLC11A1 (SLC), gallinacin 6 (GAL6) and liver-expressed antimicrobial peptide (LEAP-2) were investigated to select the best feed formulation for the broilers. These immunity genes were chosen as they can provide natural resistance to diseases and pathogens. The gene expression is highly regulated by amino acids that are basic constituents of cellular protein whereby different variations of amino acids in the diet can affect the gene expression. A total of 300 broilers (Cobb500) were tested with ten different dietary treatments. The chickens were fed with two types of diet; starter and finisher and the effects on growth performance were determined. The lysine and methionine levels were manipulated to high, standard and low based on the recommended diet for Cobb500 broilers. Treatment one is the control that consists of diet with standard levels of lysine, methionine and crude protein as recommended by Cobb-Vantress for Cobb500 broilers. Following that, ribonucleic acid (RNA) was extracted from the small intestine (jejunum), spleen and liver and used to study the gene expression of the immunity genes with real-time polymerase chain reaction (qPCR) using SYBR Green assay. The results from the growth performance of the broilers showed that increasing lysine by 0.2% in a low crude protein diet gave the best results in terms of feed conversion ratio of 1.96 ± 0.11. Meanwhile, gene expression studies on MUC2 gene in the jejunum showed overall upregulation across all dietary treatments with treatment 3 (T3) showing the highest expression with increment of 3.8-fold as compared to the control. This indicates that the mucins are not only important as a defence mechanism but also display a capacity to uptake nutrients for the rest of the body making it sensitive to dietary intake of amino acids and crude protein. Other genes expressed in spleen and liver such as SLC, GAL6 and LEAP-2 were mostly down regulated across the treatment groups as compared to the control group. These three genes offer innate immunity which recognizes different types of pathogens to prevent infection and may not be as sensitive to dietary intake of lysine and methionine as compared to MUC2 gene. In conclusion, treatment with increased lysine content by 0.2% with normal level of methionine performed better in a low crude protein diet in terms of having the lowest feed conversion ratio and highest upregulation of MUC2 gene.